Exploring temporal trends and risk factors for resistance in Escherichia coli-causing bacteraemia in England between 2013 and 2018: an ecological study. (17th December 2021) - Aliabadi, Shirin; Jauneikaite, Elita; Müller-Pebody, Berit; Hope, Russell; Vihta, Karina-Doris; Horner, Carolyne; Costelloe, Céire E
Abstract: Background: Escherichia coli are Gram-negative bacteria associated with an increasing burden of antimicrobial resistance (AMR) in England. Objectives: To create a comprehensive epidemiological picture of E. coli bacteraemia resistance trends and risk factors in England by linking national microbiology data sources and performing a longitudinal analysis of rates. Methods: A retrospective observational study was conducted on all national records for antimicrobial susceptibility testing on E. coli bacteraemia in England from 1 January 2013 to 31 December 2018 from the UK Health Security Agency (UKHSA) and the BSAC Resistance Surveillance Programme (BSAC-RSP). Trends in AMR and MDR were estimated using iterative sequential regression. Logistic regression analyses were performed on UKHSA data to estimate the relationship between risk factors and AMR or MDR in E. coli bacteraemia isolates. Results: An increase in resistance rates was observed in community- and hospital-onset bacteraemia for third-generation cephalosporins, co-amoxiclav, gentamicin and ciprofloxacin. Among community-acquired cases, and after adjustment for other factors, patients aged >65 years were more likely to be infected by E. coli isolates resistant to at least one of 11 antibiotics than those aged 18–64 years (OR: 1.21, 95% CI: 1.18–1.25; P < 0.05). In hospital-onset cases, E. coli isolates from those aged 1–17 years were more likely to be resistant than those aged 18–64 years (OR: 1.33, 95% CI: 1.02–1.73; P < 0.05). Conclusions: Antibiotic resistance rates in E. coli -causing bacteraemia increased between 2013 and 2018 in England for key antimicrobial agents. Findings of this study have implications for guiding future policies on a prescribing of antimicrobial agents, for specific patient populations in particular.